2017
DOI: 10.3390/atmos8120237
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Regional Enstrophy and Block Intensity as a Measure of Kolmogorov Entropy

Abstract: Enstrophy in a fluid relates to the dissipation tendency in a fluid that has use in studying turbulent flows. It also corresponds to vorticity as kinetic energy does to velocity. Earlier work showed that the integrated regional enstrophy (IRE) was related to the sum of the positive Lyapunov exponents. Lyapunov exponents are the characteristic exponent(s) of a dynamic system or a measure of the divergence or convergence of system trajectories that are initially close together. Relatively high values of IRE deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 32 publications
2
36
0
1
Order By: Relevance
“…This result is consistent with the results of [31,34]. In the future, in order to expand on this work it is possible to introduce the [14] probabilistic forecast to increase accuracy in blocking intensity and onset; •…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This result is consistent with the results of [31,34]. In the future, in order to expand on this work it is possible to introduce the [14] probabilistic forecast to increase accuracy in blocking intensity and onset; •…”
Section: Discussionsupporting
confidence: 87%
“…To test this proposal correlation was performed with and without a time lag of each variable up to 72 h as in [34]. There were no positive correlations when BI led IRE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies (e.g., [19][20][21]) also demonstrate that such flow regime behavior occurs independently in each of the major NH ocean basins. Additionally, Jensen et al [22] (and references therein) demonstrated that quantities such as enstrophy (specifically the measure developed by [23] called area integrated enstrophy-IE) can be utilized to identify the transitions between hemispheric or regional flow regimes. They [22] showed a correspondence between IE and entropy (Kolmogorov-Saini or metric entropy), which is related to flow predictability and stability, as well as block intensity (BI-as in [22]).…”
Section: Introductionmentioning
confidence: 99%